Dynamic bending and rotation sensing based on high coherence interferometry in multicore fiber. (March 2021) - Azmi, A.I.; Abdullah, A.S.; Mohd Noor, M.Y.; Ibrahim, M.H.; Raja Ibrahim, R.K.; Tan, Tao; Zhang, Jianzhong
Highlights: Novel sensor based on high coherence interferometry in multicore fiber. High sensitivity of 629 fringe/m −1 (curvature) and 6.2 fringe/° (rotation). Smallest curvature detection of 0.0032 m −1 (or radius of 312 m). High repeatability and linearity, insensitive to slow varying perturbation. Abstract: Bending and rotation sensing based on high coherence interferometry in seven-core fiber (SCF) is proposed here for the first time. In the suggested scheme, distinct optical paths are formed from the selected cores, thus creating a very compact in-fiber Michelson interferometer. The interferometer consists of an in-line taper structure fabricated on the SCF for a light splitting/coupling element, and a Faraday rotating mirror used as a reflective element. Different strains are exerted on the reference and sensing cores because of the dissimilar distance from the neutral axis. The phase difference between these two interferometer arms resulting from the variations in strain is resolved using a fringe counting technique. The proposed sensor is revealed to be extremely sensitive for curvature and rotation measurement, with sensitivities of 629 fringe/m −1 and 6.2 fringe/°, respectively. The sensor is capable of detecting the smallest curvature of 0.0032 m −1 or radius of 312 m. The sensor also responds linearly to rotation, with a sensitivity of 6.2 fringe/°. This response is highly repeatable; linear; insensitive to slow-varying parameters, such as temperature; and promising for the detection of direction. The proposed sensor is particularly attractive for robotics, wearable medical devices, and structural health-monitoring applications.